This Year’s Bioethicist: From Influencer to Prophetic Educator - Kuczewski, Mark (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Professional bioethicists have gained increasing acceptance in the healthcare and academic communities of the United States over the last 50 years. However, since the current administration took office in January 2025, questions concerning the appropriate role of bioethicists in preserving the values and ethics of healthcare and academic institutions have abounded. I argue that the usual tripartite characterization of service, scholarship and education still apply but how we interpret those roles and their relative importance has changed. While our established role of influencers of institutional policies remains important, the climate of fear-induced silence challenges us to emphasize our prophetic voice in calling the healthcare professions and institutions to remain faithful to their fundamental values. Furthermore, I recommend a renewed emphasis on basic education of professionals to solidify their formation.